2023
DOI: 10.3390/antiox12071381
|View full text |Cite
|
Sign up to set email alerts
|

Radical-Driven Methane Formation in Humans Evidenced by Exogenous Isotope-Labeled DMSO and Methionine

Abstract: Methane (CH4), which is produced endogenously in animals and plants, was recently suggested to play a role in cellular physiology, potentially influencing the signaling pathways and regulatory mechanisms involved in nitrosative and oxidative stress responses. In addition, it was proposed that the supplementation of CH4 to organisms may be beneficial for the treatment of several diseases, including ischemia, reperfusion injury, and inflammation. However, it is still unclear whether and how CH4 is produced in ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…ROS serve essential roles in cell signaling processes; consequently, excessive neutralization of ROS by antioxidants can disrupt these signaling processes, affecting pathways mediated by intracellular messengers, such as NO, CO, H 2 S, and the recently described CH4. In this Special Issue, Keppler et al [57] showed the capability of eukaryotic cells to synthesize CH4 via a radical-driven process. In addition, Horváth et al [58] demonstrated that although CH4 is synthesized in a radical-dependent way, it protects mitochondrial function and maintains Ca 2+ homeostasis.…”
Section: Antioxidants Interfere With Cell Signalingmentioning
confidence: 99%
“…ROS serve essential roles in cell signaling processes; consequently, excessive neutralization of ROS by antioxidants can disrupt these signaling processes, affecting pathways mediated by intracellular messengers, such as NO, CO, H 2 S, and the recently described CH4. In this Special Issue, Keppler et al [57] showed the capability of eukaryotic cells to synthesize CH4 via a radical-driven process. In addition, Horváth et al [58] demonstrated that although CH4 is synthesized in a radical-dependent way, it protects mitochondrial function and maintains Ca 2+ homeostasis.…”
Section: Antioxidants Interfere With Cell Signalingmentioning
confidence: 99%
“…A significant portion of global CH4 emissions originates from biotic sources, exceeding contributions from abiotic sources like fossil fuel and biomass burning, as well as geogenic processes [2,3] Contrary to the earlier belief that biotic CH4 production occurs exclusively under anaerobic conditions by methanogenic archaea in environments such as wetlands, landfills and rice paddies, and in the digestion system of termites and ruminants, recent research has revealed that biotic CH4 can also be produced in the presence of oxygen (O2). The first evidence of CH4 formation by plants under aerobic conditions was presented by [4], and subsequent research expanded this finding to a range of eukaryotic CH4 and prokaryotic sources, including mosses and lichens [5], marine algae [6,7], terrestrial and marine cyanobacteria [8], plant cell cultures [9,10], non-methanogenic archaea [10], animals [11,12], human cell cultures and humans [10,[13][14][15][16], as well as fungi [10,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the earlier assumption that biotic CH 4 production occurs exclusively under anaerobic conditions by methanogenic archaea in certain environments, such as wetlands, landfills, and rice paddies, and in the digestion system of termites and ruminants, recent research has revealed that biotic CH 4 can also be produced in the presence of oxygen (O 2 ). The first evidence of aerobic CH 4 formation by plants was presented by Keppler et al [4], and subsequent research expanded this finding to a range of eukaryotic CH 4 and prokaryotic sources, including mosses and lichens [5], marine algae [6,7], terrestrial and marine cyanobacteria [8], plant cell cultures [9,10], non-methanogenic archaea [10], animals [11,12], human cell cultures, and humans [10,[13][14][15][16], as well as fungi [10,17,18].…”
Section: Introductionmentioning
confidence: 99%